Sistem Keamanan Rumah Yang Dapat Dikendalikan Melalui Android - Azis, Elang Abdul; Hidayat, Rahmat; Yulindon, Yulindon (JURNAL TEKNIK INFORMATIKA, 2020)
The number of theft and increased crime makes many people afraid to leave the house because of the many crimes, therefore I aim to solve the problem in this case by creating a home control tool that can be controlled via Android. So people do not need to be afraid to leave the house because it can be controlled through Even great distances, of course this is very helpful in the problem of crime and can reduce crime rates